Insights into Fertility Variability in Africa: A Path Toward Achieving the SDGs - Nelson Doe Dzivor; Alice C. Mensah; Edith Mensah; Moses Odamtten (Pan-African Journal of Health and Environmental Science)
Background: The Total Fertility Rate (TFR) is a major demographic index used to measure population growth. This indicator (TFR) varies significantly across Africa. This variation is influenced by cultural, economic, and policy-related factors.